Consequence of alcohol intoxication-mediated efferocytosis impairment - Brahadeeswaran, Subhashini; Tamizhselvi, Ramasamy (Frontiers in Immunology, 2024)
Alcohol ingestion is a widespread habituation that evolved along with a growing population, altering physiological conditions through immunomodulatory function. There is much research that has reported that consumption of alcohol at low and heavy levels causes different biological impacts, including cellular injury, leading to systemic dysfunction and increased inflammatory markers. In the fate of professional phagocytic cells, efferocytosis is an inevitable mechanism activated by the apoptotic cells, thus eliminating them and preventing the accumulation of cell corpses/debris in the microenvironment. Subsequently, it promotes the tissue repair mechanism and maintains cellular homeostasis. Unfortunately, defective efferocytosis is widely found in several inflammatory and age-related diseases such as atherosclerosis, autoimmune diseases, lung injury, fatty liver disease, and neurodegenerative diseases. Alcohol abuse is one of the factors that provoke an immune response that increases the rate of morbidity and mortality in parallel in systemic disease patients. Information regarding the emergence of immunomodulation during alcoholic pathogenesis and its association with efferocytosis impairment remain elusive. Hence, here in this review, we discussed the mechanism of efferocytosis, the role of defective efferocytosis in inflammatory diseases, and the role of alcohol on efferocytosis impairment.